História da Inquisição Portuguesa. (1536-1821) - Ana Isabel López Salazar (2015)
The historiography of the Portuguese Inquisition is experiencing a moment of great expansion, both in terms of the quantity and the quality of most of the works written about the subject. The body of scientific studies has been steadily increasing since the 1980s and the different research lines have been gradually filling in a significant part of the gaps relating to what was still unknown about the Inquisition early on in that decade. There are several reasons for this and it is not my intention to list them all here. First of all, the peak of quantitative history resulted in attempts to measure the rhythms of inquisitorial repression in an accurate way.